A Partnership Among Local Public Health Agencies, Elementary Schools, and a University to Address Childhood Obesity: A Scalable Model of the Assess, Identify, Make It Happen Process - Ingman, Benjamin C.; Loecke, Carla; Belansky, Elaine S. (Frontiers in Health Services, 2022)
Background One pathway to addressing childhood obesity is through implementing evidence-based practices (EBPs) shown to promote nutrition and physical activity in K-12 school settings. Assess, Identify, Make it happen (AIM) is a strategic planning process to engage stakeholders in implementing EBPs in their K-12 schools. Local Public Health Agencies (LPHAs) are a potential partner to facilitate this process to a broader audience of rural school communities. Methods A process and outcome evaluation design was applied in this study to examine the extent to which LPHAs effectively implemented AIM with rural/frontier schools in comparison to university staff. Data collection included post-meeting surveys completed by facilitators, a post-intervention interview with facilitators, a survey of school task force members at the end of the AIM process, and systematic documentation of the intervention. Results Reach—Among the 26 eligible elementary schools, 18 (69%) agreed to participate. Effect—In total, schools facilitated by LPHAs fully implemented an average of 4.0 changes per school, while schools facilitated by the university staff fully implemented an average of 3.7 changes. Adoption—Among the five LPHAs in the target region, all five agreed to partner on the initiative, but some agencies were unable to identify sufficient personnel to facilitate all schools in their catchment area. Implementation—(1) In total, 89 of 94 (95%) meetings scheduled by LPHA facilitators occurred. 47 of 48 (98%) meetings scheduled by the university staff occurred. (2) The university staff self-reported 93% of agenda items in the AIM process as “completely” followed while LPHA facilitators reported 41% of agenda items as “completely” followed. (3) Task force satisfaction with the AIM process and facilitator showed limited variance across LPHAs and university-facilitated schools. Maintenance—Of the 16 school districts that agreed to participate in the school-based version of AIM, 9 (56%) also participated in a district-wide version of AIM 2 years later. Conclusion AIM is an effective process for implementing EBPs in elementary schools when facilitated by LPHAs. Effective partnerships, a nuanced approach to fidelity, scalability considerations, and the role of technical assistance and training all contributed to the successful implementation of this LPHA-Elementary school partnership.